2010
DOI: 10.1016/j.jvs.2009.11.077
|View full text |Cite
|
Sign up to set email alerts
|

Insulin use is associated with poor limb salvage and survival in diabetic patients with chronic limb ischemia

Abstract: Diabetic patients who present with limb ischemia can be subdivided into three distinct subgroups based on their diabetic regimen. The survival and LS rates of those controlled with diet or OM are nearly identical to nondiabetics, both of which are significantly better than OM+INS or INS. The PP rate in endovascular-treated patients is worse in patients who are on insulin. Being on insulin is independently associated with decreased survival and limb loss but not PP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 35 publications
2
25
3
2
Order By: Relevance
“…A few recent studies reported that poor glycemic control 10,11) and insulin use 19) were associated with limb prognosis in CLI patients, but each study adopted only one DM-related variable and lacked adjustment for other diabetic conditions, including diabetic duration. DM patients under insulin therapy would tend to have a longer diabetic duration and a poorer glycemic control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few recent studies reported that poor glycemic control 10,11) and insulin use 19) were associated with limb prognosis in CLI patients, but each study adopted only one DM-related variable and lacked adjustment for other diabetic conditions, including diabetic duration. DM patients under insulin therapy would tend to have a longer diabetic duration and a poorer glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, insulin therapy in DM patients, leading to hyperinsulinemia, could result in atherosclerosis and have an unfavorable effect on cardiovascular outcomes 17,18) . One group recently reported that insulin use at the time of revascularization was associated with a poor prognosis in diabetic patients with CLI 19) but their study lacked adjustment for other DM-related conditions, that is, diabetic duration and glycemic control. Epidemiological studies have demonstrated that diabetic patients under insulin therapy often had a longer diabetic duration than those without insulin therapy and that they also tended to have a poorer glycemic control [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Major randomised intervention trials of blood-glucose-lowering or anti-hypertensive therapies in populations with diabetes mellitus have shown limited reductions in neuropathy and/or macrovascular disease and no benefi t on amputation rates [11]. Outcomes of diabetic patients who presented with limb ischaemia was shown to be associated to their diabetic regimen [12]. In a US study, the survival and limb salvage rates of those controlled by diet or oral medication were signifi cantly better than oral medication + insulin or insulin alone.…”
Section: Discussionmentioning
confidence: 99%
“…Однако в 2015 году этот по-казатель уже превысил прогнозируемый более чем на 100 миллионов человек [1,2]. Обеспокоенность вызывает прогрессирующий рост числа больных, страдающих от органоспецифических осложнений, обусловленных недостаточным качеством метабо-лического контроля [3][4][5]. При всем многообразии факторов, влияющих на изменения метаболических процессов, одним из ведущих остается формирую-щаяся гипоксия вследствие инсулиновой недоста-точности [6][7][8].…”
unclassified